2014
DOI: 10.1039/c3ob41798k
|View full text |Cite
|
Sign up to set email alerts
|

The acid-catalysed synthesis of 7-azaindoles from 3-alkynyl-2-aminopyridines and their antimicrobial activity

Abstract: The synthesis of 7-azaindoles from 3-alkynyl-2-aminopyridines using acidic conditions, namely, a mixture of trifluoroacetic acid (TFA) and trifluoroacetic anhydride (TFAA), is described. This methodology resulted in the synthesis of fifteen 7-azaindoles, with most containing substituents at the 2- and 5-positions. The majority of these were tested for antimicrobial activity against a range of bacteria and yeasts. The 7-azaindoles displayed the best activity against the yeasts, particularly against Cryptococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…7 During the course of this work we were able to show that through the use of the Sonogashira coupling reaction using dihalogenated aminopyridines we were able to introduce two acetylenes onto a 2-aminopyridine nucleus (Fig. 2).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…7 During the course of this work we were able to show that through the use of the Sonogashira coupling reaction using dihalogenated aminopyridines we were able to introduce two acetylenes onto a 2-aminopyridine nucleus (Fig. 2).…”
Section: Resultsmentioning
confidence: 97%
“…For this purpose we found that the use of potassium t-butoxide in a mixture of DMF and THF was the best method to afford the desired azaindoles 15a-e, rather than the acid-mediated methodology we had developed. 7 We were now in a position to apply another Sonogashira coupling reaction to the bromoazaindoles 15a-e. Conducting the reaction on 15a-e at reflux led to the formation of 16a-e, which was subjected to conditions (TBAF) for the removal of the TMS substituent to furnish 17a-e (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…They have attracted considerable interest from the chemical community because of their potential applications in natural product synthesis and pharmaceuticals due to their hydrogen bonding properties and excellent water solubility. The 1H-pyrrolo [2,3-b]pyridine moiety exhibits a broad spectrum of biological activities, including anticancer [2], antitumor [3][4][5], anti-angiogenic [6], antimicrobial [7], as inhibitor of HIV-1 [8,9] and cell division cycle of 7-kinase [10], antifungal [11], analgesic [12], antimalarial [13], antiproliferative [14,15], antibacterial [16], reducing chronic pain [17], as cisplatin and transplatin derivatives [18], antimycobacterial [19], as Topoisomerase I inhibitors [20] and protein kinase inhibition [21], etc. Azaindole and its core containing compounds which include neocryptolepine (1), variolin-B (VAR-B) (2) and grossularines (3) are natural products, while 7-aza-rebeccamycin (4) and 5-azaellipticine (5) are of synthetic origin, whose activity is related to DNA, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Currently the most common routes for the synthesis of 7-azaindoles and their derivatives are, first of all, various modifications of Madelung and Reissert syntheses [2], as well as palladium-catalyzed processes based on 2-aminopyridine [10], and, secondly, the annelation of pyridine ring to pyrrole ring [2,11]. _______ *Dedicated to Academician of the Russian Academy of Sciences Yu.…”
mentioning
confidence: 99%